Launch sequencing of pharmaceuticals with multiple therapeutic indications: evidence from seven countries - Mills, Mackenzie; Michaeli, Daniel; Miracolo, Aurelio; Kanavos, Panos (BMC health services research, 2023)
New medicines are increasingly being identified as efficacious across multiple indications. The impact of current pricing and reimbursement policies on launch decisions across these indications remains unclear.